Effects of land-based sources on water quality in the Omerli reservoir (Istanbul, Turkey) - (:unkn) unknown (SPRINGER, 2009)
The Omerli reservoir is located on the northeastern side of the Istanbul City. It is one of the most important sources of drinking water with a surface area of 23.1 km(2) and a volume of 220 x 10(6) m(3) in the Marmara Region. Water quality characteristics of the lake investigated from May 2002 to April 2003 enabled us to identify the effect of waste loads on water quality of Omerli Lake. The following parameters were measured in the lake water: temperature (16.1A degrees C), conductivity (250 mu S/cm), secchi disk depth (1.9 m), dissolved oxygen (DO) (9.36 mg/L), nutrients [ortho-phosphate (78.9 mu g/L), nitrate + nitrite (707.5 mu g/L) and ammonia-nitrogen (264 mu g/L)], chlorophyll a (9.43 mu g/L), total organic carbon (3.33 mg/L), total suspended solids (4.54 mg/L), total poly aromatic hydrocarbon (t-PAH) (0.69 mu g/L) and copper (24.5 mu g/L). T-PAH (16.5 mg/g-dry-w), Cu (96.5 mu g/g-dry-w), organic carbon (org-C) (2.0%) and N (0.44%) were determined in the surface sediment. The values of chlorophyll a and DO in the upper layer were relatively high and low secchi disk depths indicates eutrophic state. There are five channels discharging water, including waste water, into the lake. All channels were sampled during six occasions in order to cover variations between seasons. The following parameters were measured: total organic carbon, total phosphorus, total kjeldahl nitrogen, ammonia and total suspended solids with the flow rates. The GoA beyli stream has the highest flow into the lake (1.5 x 10(8) m(3)/year) but most of the nutrients were discharged from the Pa angstrom akoy channel. It is accounting for 81% of ammonia and 80% of total phosphorus into the lake. Three scenarios were run using AQUATOX model: (1) all existing inflows are discharging into the lake (present situation); (2) none is discharging; (3) all are discharging except the Pa angstrom akoy channel. The first scenario produced concentrations consistent with measurements in the lake. In all stations, a phytoplankton peak value was predicted during November and December 2002, and January 2003. In the second scenario, as expected, a significant decrease in the concentrations was predicted. In the third scenario, a small improvement in the water quality was obtained. To significantly improve the state of the lake, instead of entering Pa angstrom akoy channel, wastewater should bypass the lake.
Keywords: Eutrophication; Lake; Nutrients; Phytoplankton; AQUATOX; Model scenarios; POLYCYCLIC AROMATIC-HYDROCARBONS; SHALLOW LAKES; EUTROPHICATION; PHOSPHORUS; POLLUTION; STATE; RESTORATION; ORIGIN; PAHS